Carlo Moreschi (1876-1921): co-founder of the journal “La Medicina del Lavoro” and often forgotten pioneer of modern medicine / Carlo Moreschi (1876-1921): co-fondatore de “La Medicina del Lavoro” e dimenticato pioniere della medicina moderna - Riva, M.A.; Smith, D.R.; Cesana, G. (La Medicina del Lavoro, 2011)
Summary Background: Carlo Moreschi (1876-1921) was founding co-editor of the journal “Il Lavoro” (now known as “La Medicina del Lavoro”), together with Luigi Devoto in 1901. Despite this fact, many of his pioneering contributions to 20th century scientific debate are not well known outside Italy. Objectives: The aim of this paper therefore was to recall Moreschi’ achievements and the groundbreaking work of this remarkable Italian physician. Methods: A comprehensive analysis was conducted on scientific papers written by Carlo Moreschi between 1901 and 1920, extending the investigation to his original manuscripts and private correspondence with family and colleagues. Results: Careful examination of Moreschi’s work reveals several studies in the field of social medicine, epidemiology of infectious diseases, general pathology and oncology. In particular, his main interest in haematology and immunology enabled Moreschi to be one of the first to understand the mechanisms of complement fixation and the formation pathways of antiglobulin sera. In this manner, Moreschi significantly contributed to the work of Wassermann regarding the diagnosis of syphilis, as well as contributing to the discovery of the “antiglobulin test”, first described by Coombs in 1945. Furthermore, Moreschi co-founded “Il Lavoro” and “Haematologica”, the oldest journals in their respective fields. Conclusions: According to Devoto, Moreschi can be remembered as the archetype modern researcher and clinician. His role in the 20th century scientific debate and his pioneering work in the field of immunology and haematology, that are often forgotten due to his premature death, deserve to be reconsidered and re-assessed by the Italian and international scientific community. Riassunto «Carlo Moreschi (1876-1921): co-fondatore de “La Medicina del Lavoro” e dimenticato pioniere della medicina moderna». Introduzione: Carlo Moreschi (1876-1921) fu il primo redattore de “Il Lavoro”, fondato da Luigi Devoto nel 1901 e nucleo originario della rivista “La Medicina del Lavoro”. I contributi offerti da questo illustre scienziato italiano al dibattito medico-scientifico di inizio Novecento sono oggi poco conosciuti. Obiettivi: Scopo del presente lavoro è quello di ricordare la vita e l’attività di ricerca scientifica di Carlo Moreschi. Metodi: È stata condotta un’analisi approfondita degli articoli scritti da Moreschi dal 1901 al 1920, estesa anche ai manoscritti originali e alle lettere scritte a colleghi e familiari. Risultati: Moreschi condusse numerosi studi innovativi nel campo della medicina sociale, dell’infettivologia, dell’oncologia e della patologia generale. In particolare, in campo immunologico fu tra i primi a comprendere i meccanismi alla base della fissazione del complemento, aprendo la strada ai lavori di Wassermann sulla sierodiagnosi della sifilide. Inoltre, per primo, lavorò sui sieri antiglobulina umana, offrendo contributi decisivi alle successive ricerche di Coombs in questo settore. Moreschi co-fondò due giornali “Il Lavoro” e “Haematologica”, entrambi tra le riviste scientifiche più antiche nelle rispettive discipline. Conclusioni: Nonostante la prematura morte, avvenuta all’età di 45 anni, la figura di questo scienziato italiano, che Devoto stesso definì “studioso geniale e clinico moderno”, necessita di una maggiore considerazione e valorizzazione da parte della comunità scientifica nazionale ed internazionale.